Genetic Association of Lipid-Lowering Drug Target Genes with Chronic Obstructive Pulmonary Disease: A Mendelian Randomization Study - Hao Luan; Tianhua Wang; Rui Wang; Yu Wang; Yu Liu; Wenru Sheng; Jiaqi Guo; Haotian Ji; Xiufeng Liu; Xiqing Xue; Yiider Tseng (COPD)
The role of lipid-lowering drugs in chronic obstructive pulmonary disease (COPD) is controversial in clinical studies. This study aimed to explore the causal relationship between lipid-lowering drugs and COPD from a genetic perspective, and to evaluate the potential effects of this relationship. Four hundred and thirty-one lipid-related phenotypes and two COPD datasets were obtained from Genome-Wide Association Studies (GWAS) and analysed together using Mendelian randomization (MR). Genetic variants associated with genes encoding targets of lipid-lowering drugs were extracted from the Global Lipid Genetics Consortium. Expression quantitative trait loci data in relevant tissues were adopted to validate lipid-lowering drug targets that reached significance. We found that four lipid abnormalities were associated with COPD risk. Genetically proxied inhibition of HMG-CoA reductase (HMGCR) and PCSK9 is associated with an increased risk of COPD. And there is a significant MR correlation between increased whole blood HMGCR expression and COPD. HMGCR and PCSK9 inhibitors are associated with onset of COPD, lung function, and COPD-associated infections. Mediation analyses were performed to explore potential mediators of how genetically proxied inhibition of HMGCR and PCSK9 influences the risk of COPD through different immune cell phenotypes and inflammatory factor levels. Our findings indicate a potential link between the use of HMGCR and PCSK9 inhibitors and increased risk of COPD and exacerbation of COPD phenotypes. This suggests effects beyond LDL-C modulation, potentially involving immune cell function and inflammatory factors.